On Contra $π gγ$-Continuous Functions - Ravi, O.; Rajasekaran, I.; Pandi, A.; Murugesan, S. (Journal of Informatics and Mathematical Sciences, 2014)
In this paper, we introduce and investigate the notion of contra $π gγ$-continuous functions by utilizing $π gγ$-closed sets [31]. We obtain fundamental properties of contra $π gγ$-continuous functions and discuss the relationships between contra $π gγ$-continuity and other related functions.